Reconceptualization of Marine Rights Granting: Decentralizing Permits, Deconcentrating Rights Determination - Dzulkarnain Alghafuru Syahputra (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2026)
The Constitutional Court Decision No. 3/PUU-VIII/2010 abolished the Coastal Waters Cultivation Rights (HP-3) on the grounds that it contradicted the public trust doctrine. However, more than a decade after this decision, new forms of private control over marine spaces have emerged, including 263 Building Use Rights certificates and 4 Freehold Title certificates in Tangerang waters, as well as sea fences restricting access for traditional fishers. This normative-doctrinal legal research aimed to analyze the full decentralization design in Law No. 27 of 2007 concerning Management of Coastal Areas and Small Islands as a form of design error from the perspective of legislation formation. Using statute, conceptual, and case approaches, this research deconstructed the authority structure that conflates administrative and juridical functions, lacks vertical checks and balances, and ignores the character of the sea as public goods. The novelty of this research lies in offering a reconceptualization through the model of decentralization of permits and deconcentration of rights determination as an institutional firewall against conspirative practices. This research concluded that Law No. 1 of 2014 and the Job Creation Law only changed the nomenclature from